2002
DOI: 10.1006/mthe.2002.0566
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Retroviral Gene Transfer Based on Centrifugation-Mediated Vector Preloading of Tissue Culture Vessels

Abstract: Efficient retroviral gene transfer into primary cells is a prerequisite for various gene therapeutic strategies. We have developed a transduction protocol based on the preloading of tissue culture vessels with retroviral particles by low-speed (1000g) centrifugation. We show that vector-preloaded tissue culture vessels allow highly efficient gene transfer into various target cells. We obtained transduction rates of up to 85% for primary T lymphocytes after just a single round of transduction. Under clinically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
3
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 20 publications
0
30
3
1
Order By: Relevance
“…Currently the most suitable of these clones is processed under GMP conditions to generate a master cell bank and subsequent retroviral supernatant for clinical use. High-titer retroviral supernatant in conjunction with efficient gene transfer protocols 12,30 will allow high transduction rates after just one infection cycle (at day 3 after initial stimulation). In combination with a selection method based on magnetic cell sorting, the whole procedure may, therefore, be shortened to 5 days.…”
Section: Transduction Resulted In High Cd34 Expression For Both Vectomentioning
confidence: 99%
“…Currently the most suitable of these clones is processed under GMP conditions to generate a master cell bank and subsequent retroviral supernatant for clinical use. High-titer retroviral supernatant in conjunction with efficient gene transfer protocols 12,30 will allow high transduction rates after just one infection cycle (at day 3 after initial stimulation). In combination with a selection method based on magnetic cell sorting, the whole procedure may, therefore, be shortened to 5 days.…”
Section: Transduction Resulted In High Cd34 Expression For Both Vectomentioning
confidence: 99%
“…It is clear that higher levels of transduction are preferable particularly with respect to use in a clinical context. Protocols have been developed that have reported high-level gene transfer using longer antibody-mediated preactivation periods (Movassagh et al, 2000), through the use of retronectin to enhance infection (Hanenberg et al, 1996) or by preloading plates with retrovirus (Kuhlcke et al, 2002). The levels of retroviral transduction generated here represent those achieved using a short period of centrifugation (spin-fection) and is adaptable to transduction on a large scale.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][30][31][32][33] However, in our systems, excellent gene transfer could be achieved by the simple addition of SeV vector solution without specific reagents or centrifugation. Moreover, optimal SeV-mediated gene transfer to activated T cells could be performed during a relatively brief exposure time (less than 30 min, Figure 4d), with representative results seen in nasal mucosa, 20 in the vasculature, 21 in retinal tissue, 24 as well as in human umbilical cord bloodderived CD34-positive cells.…”
Section: Activated T-cell-directed Gene Transfer Via Sevmentioning
confidence: 99%
“…Although an encouraging human study using a retrovirus demonstrated the success of T-cell-directed gene therapy against severely combined immunodeficiency disease (SCID) owing to adenosine deaminase deficiency (ADA), 1,3 it has been difficult to use this strategy in cases of other diseases, because the gene transfer efficiency is usually a critical factor limiting the outcome. Therefore, current efforts are now focused on the development of pseudotyped vectors 4 and transduction techniques [5][6][7][8] for the use of retroviral vectors for clinical applications.…”
Section: Introductionmentioning
confidence: 99%